2012
DOI: 10.1002/ange.201201176
|View full text |Cite
|
Sign up to set email alerts
|

G‐Rich Sequence‐Specific Recognition and Scission of Human Genome by PNA/DNA Hybrid G‐Quadruplex Formation

Abstract: Ein Ass: Eine einzige Peptidnucleinsäure (PNA) adressiert effektiv die G‐reiche Region in doppelsträngiger DNA durch Bildung eines PNA/DNA‐Hybrid‐G‐Quadruplex. Nur eine Zielposition im gesamten menschlichen Genom wurde selektiv durch den Hybrid‐G‐Quadruplex gespalten. Eine solche positionsselektive DNA‐Spaltung ist entscheidend für Genmanipulationen in der Molekularbiologie, Biotechnologie und Therapie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…PNAs have been initially developed for hybridization to duplex DNA for a higher thermodynamic stability of PNA–DNA duplexes compared to DNA–DNA duplexes. Various PNA oligomers have been reported to recognize noncanonical DNA/RNA G-quadruplexes (G4) by forming heteroduplexes or heteroquadruplexes. Phan et al reported that guanine-linked PNA can stabilize a particular G4 by dual recognition . Panyutin and co-workers illustrated short PNA oligomers can induce BCL2 G4 formation using C-strand-invading short PNAs .…”
Section: Introductionmentioning
confidence: 99%
“…PNAs have been initially developed for hybridization to duplex DNA for a higher thermodynamic stability of PNA–DNA duplexes compared to DNA–DNA duplexes. Various PNA oligomers have been reported to recognize noncanonical DNA/RNA G-quadruplexes (G4) by forming heteroduplexes or heteroquadruplexes. Phan et al reported that guanine-linked PNA can stabilize a particular G4 by dual recognition . Panyutin and co-workers illustrated short PNA oligomers can induce BCL2 G4 formation using C-strand-invading short PNAs .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous reports have shown that PNA is capable of sequence-specific binding to DNA, obeying the Watson-Crick pattern, to form a double helix [12, 13]. PNA may also recognize particular DNA sequences to generate other complex yet specific helical structures such as triplex or quadruplex [1416]. For example, a unique “P-form” triple helix conformation comprising two polypyrimidine PNAs and one polypurine DNA can be achieved via combination of Watson–Crick and Hoogsteen base interactions [14].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting quadruplexes were found to consist of two PNA and two DNA molecules (i.e., the stoichiometry of DNA to PNA was 1:1). Later the double invasion was used for sequence-specific scission of a double-stranded plasmid and genomic DNA [14]. However, the strand arrangements and stoichiometry of the DNA-PNA quadruplex complexes were not determined in these studies.…”
mentioning
confidence: 99%